El conocimiento y su Relación con la Filosofía, la Realidad y el Lenguaje - Matos, José Concepción; Ojeda-de-López, Juana Cecilia; Rodríguez, Miryan David; Jiménez-Barriosnuevo, María-del-Carmen (EPISTEME KOINONIA, 2021)
El conocimiento y su Relación con la Filosofía, la Realidad y el Lenguaje